Identification of Watershed Conditions and Formulation of Watershed Management Strategies : Case Study in: Musi-Sugihan-Banyuasin-Lemau River Basin, South Sumatra Province - Maman Noprayamin; Anis Saggaff; Arie Setiadi Moerwanto; Kiagus Muhammad Aminuddin (Universitas Medan Area, 2023)
In Indonesia, 39 watersheds were deemed essential in 1994, and the importance of watersheds grew in 2000. The existence of a watershed has the role of being able to sustain water availability, maintain the balance of the ecosystem and as a container for flowing water. The Musi-Sugihan-Banyuasin-Lemau River Area (WS MSBL), which has an area of 86680 km2 and is made up of 23 primary watersheds, is one of the largest watersheds in the Sumatra region. Research was done to determine the state of the watershed so that a strategy for watershed conservation could be chosen. In-depth interviews with stakeholders in the form of focus group discussions (FGD) were utilized as the study method to collect both secondary and primary data about the circumstances of the watershed as well as to gain in-depth management outcomes. The study's findings demonstrate that managing the WS MSBL watershed involves more than only technical issues; it also necessitates involving associated institutions and stakeholders, necessitating the creation of operational watershed management strategies.